2021
DOI: 10.3390/app11135910
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Insulating Sustainable Mortars with Ampelodesmos mauritanicus and Pennisetum setaceum Plants as Aggregates

Abstract: The use of natural fibers in cement composites is a widening research field as their application can enhance the mechanical and thermal behavior of cement mortars and limit their carbon footprint. In this paper, two different wild grasses, i.e., Ampelodesmos mauritanicus, also called diss, and Pennisetum setaceum, also known as crimson fountaingrass, are used as a source of natural aggregates for cement mortars. The main purpose is to assess the possibility of using the more invasive crimson fountaingrass in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Overall, natural fibers with high cellulose content and small microfibril angles, having high crystallinity index, more compact and homogeneous morphology as well as low ash and water contents are the most suitable for the manufacturing of biocomposites with good mechanical performances [58,59].…”
Section: Tensile Testmentioning
confidence: 99%
“…Overall, natural fibers with high cellulose content and small microfibril angles, having high crystallinity index, more compact and homogeneous morphology as well as low ash and water contents are the most suitable for the manufacturing of biocomposites with good mechanical performances [58,59].…”
Section: Tensile Testmentioning
confidence: 99%
“…Among the first use, the cultivation of these plants in wetlands built for the treatment of wastewater has been investigated [8], as well as electrogenesis mediated by the rhizosphere of the plants [9]. Regarding the second use, it stands out for potential application as a natural aggregate for cement mortars (up to 30 wt% of fiber), using treatment with hot water [10]. However, this previous work concluded that a chemical treatment was needed to improve the compatibility between the cement and the fiber.…”
Section: Introductionmentioning
confidence: 99%